Variations of shape, length, branching, and end trunks of M1 segment of middle cerebral artery - Valvita Reci; Sadi Bexheti (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2019)
Introduction: The middle cerebral artery is divided into four segments: proximal M1, insular M2, opercular M3 and cortical M4. M1 extends from the bifurcation point of ACI at ACA and ACM to the insula threshold, laterally from chiasma opticum, laterally from tractus opticus and caudally from trigonum olfactorium, directed laterally, dorsally and rostrally.